Paradise lost : [large type] and, Paradise regained - Milton, John, 1608-1674 (Kennebec Large Print perennial favorites collection., 2011)
Paradise Lost is Milton's 1667 epic poem about the Creation and the Fall. In 1671, John Milton published Paradise Regained, telling of Jesus' triumphant resistance to Satan's temptation, regaining the Paradise lost by Adam and Eve.